(untitled) (Bangladesh Journal of Zoology, 2022)
Coccids are amongst the most destructive pests of horticultural, agricultural, household ornamental plants, and wild plants in varying degrees. To evaluate the prevalence of its fauna in Jahangirnagar University Campus (JUC), Savar, Dhaka, Bangladesh, a year-long study was conducted from September 2004 to August 2005, by visual counting in regular fortnightly visits. A total of 99755 insects of 13 coccid species were recorded from 12 study sites. They infested 41.2% plants of 786 individuals under 17 host plant species. Coccid incidence varied greatly according to seasons, plant numbers, and study sites. Significant differences were observed in the mean number of coccid fauna (F = 3.87, df = 12, P < 0.05) in different study sites. The highest infestation was observed by Ferrisia virgata followed by Chloropulvinaria pisdii, Planococcus pacificus, Perissopneumon ferox, Icerya aegyptiaca, Aspidiotus destructor, Crypticerya jacobsoni, Icerya minor, Rastrococcus spinosus, Pseudococcus citriculus, Maconellicoccus hirsutus, Cerococcus indicus, and Coccus hesperidum. The total number of plants present in the study sites was positively correlated with the total infested plants (r = 0.451). Highly infested plants attracted more insects than less infested plants (r = 0.813). The coccid population started to increase after the winter season and maintained a steady level up to the end of the rainy season (March to August). All study sites contained insect populations but SS-6, 7, 8, and 10 harbored significantly higher numbers of them. Rain did not make any significant differences (F = 1.445, df = 11, P = 0.168) in the pest infestation. The mean number of coccids at different months was positively correlated with the monthly average temperature (r = 0.390) and relative humidity (r = 0.412). The present findings may help in designing an integrated coccid management system. Bangladesh J. Zool. 50 (1): 67-82, 2022